Correlation Degree Analysis of Tourism and Economic Growth Based on Computable General Equilibrium Model - Meng Li (Journal of Mathematics)
With the globalization of the world economy and the improvement of people’s living standards, tourism has become a “sunrise industry” in the modern economy. Around the world, tourism is becoming an important lifestyle and socio-economic activity in modern human society, and showing a good development trend. With the continuous growth of tourist sources, the continuous expansion of industrial scale, the continuous publicity of tourism demand personality, the increasing enrichment of tourism products, the integration of market competition into every link of service, the gradual improvement of tourism quality and level, the widespread application of network, the rapid intensification of technological innovation for Tourism, the promotion of traditional culture, and the increasingly prominent cultural competition in tourism, Popular group tourism stands out. Whether in developed or developing countries, tourism plays an increasingly significant role in promoting social and economic development. It is particularly important to quantify the contribution of tourism in the national economy and which industries are better developed by tourism. It is of great significance for each tourism region and each region to formulate corresponding strategies for the development of current scenic spots, and also plays a greater role in promoting the coordinated development of tourism. By analyzing a large number of relevant data, according to the relevant research theories of tourism economics and the contribution of tourism development to the economy at home and abroad, firstly, this paper analyzes the development status of tourism resources in Gansu Province, and uses the time series analysis method to obtain the pulling effect of the increase of Tourism income on the economy; Secondly, the grey correlation degree is used to quantitatively analyze the relationship between tourism and other industries; Finally, according to the conclusion of the article and the research results of many scholars, this paper puts forward the Countermeasures of how to better develop tourism and promote economic development to a greater extent. The development of tourism has a very important impact on expanding social demand.